Y a usted... ¿le sobre la plata? Determinantes de los precios minoristas en el mercado de gasolina, en Lima Metropolitana - Ruiz Díaz, Gonzalo (2003)
This paper provides some empirical findings about competition and pricing in retailgasoline markets in Lima. Through the estimation of reaction curves for a sample of 84 gasolinestations located in 22 districts of the city, the paper shows the influence of supply and demandfactors on gasoline prices, during the period February, 1999 - January, 2000. The main findingswere the abscence of strong price competition and the presence of strong interbranddifferentiation in this market. The results also show the high influence of location andtechnology as determinants of gasoline prices. This evidence contribute to explain the high pricedifferentials commonly observed in these markets and the influence of horizontal differentiationon pricing policies of retailers.